The Research on Chinese Synonyms Learning in Foundation Chinese at Assumption University - Kangwansurakrai , Tawan (Journal of Sinology (วารสารจีนวิทยา), 2014)
The target of this research was Thai undergraduates from Assumption University who study foundation Chinese courses. The focus is on Chinese synonyms studying at Assumption University which is an international University which means all courses are taught in English. The study has chosen certain synonyms from the foundation Chinese textbooks used in the university. The research finding shows that the students’ errors in synonyms usage can be classified into 4 types: the negligence of the synonym’s scope of usage, the overlook of the synonym’s emphasis points, the mismatch of collocation terms and the negligence of the synonym’s syntax function. The main causes for such errors are the influence of English as a medium of the instruction, the influence of mother tongue (Thai) and the methods student applied to Chinese synonyms learning.